Foxp3 silencing with antisense oligonucleotide improves immunogenicity of an adjuvanted recombinant vaccine against sporothrix schenckii - Batista-Duharte, Alexander [UNESP]; Sendra, Luis; Herrero, Maria José; Portuondo, Deivys Leandro [UNESP]; Téllez-Martínez, Damiana [UNESP]; Olivera, Gladys; Fernández-Delgado, Manuel; Javega, Beatriz; Herrera, Guadalupe; Martínez, Alicia; Costa, Paulo Inacio [UNESP]; Carlos, Iracilda Zeppone [UNESP]; et al. (My University, 2021)
Background: In recent years, there has been great interest in developing molecular adjuvants based on antisense oligonucleotides (ASOs) targeting immunosuppressor pathways with inhibitory effects on regulatory T cells (Tregs) to improve immunogenicity and vaccine efficacy. We aim to evaluate the immunostimulating effect of 2′OMe phosphorothioated Foxp3-targeted ASO in an antifungal adjuvanted recombinant vaccine. Methods: The uptake kinetics of Foxp3 ASO, its cyto-toxicity and its ability to deplete Tregs were evaluated in murine splenocytes in vitro. Groups of mice were vaccinated with recombinant enolase (Eno) of Sporothix schenckii in Montanide Gel 01 adjuvant alone or in combination with either 1 µg or 8 µg of Foxp3 ASO. The titers of antigen-specific antibody in serum samples from vaccinated mice (male C57BL/6) were determined by ELISA (enzyme-linked immunosorbent assay). Cultured splenocytes from each group were activated in vitro with Eno and the levels of IFN-γ and IL-12 were also measured by ELISA. The results showed that the anti-Eno antibody titer was significantly higher upon addition of 8 µM Foxp3 ASO in the vaccine formulation compared to the standard vaccine without ASO. In vitro and in vivo experiments suggest that Foxp3 ASO enhances specific immune responses by means of Treg depletion during vaccination. Conclusion: Foxp3 ASO significantly enhances immune responses against co-delivered adjuvanted recombinant Eno vaccine and it has the potential to improve vaccine immunogenicity.
Keywords: Antisensense oligonucleotide; Foxp3; Regulatory T cells; Sporothrix schenckii; Vaccine immunogenicity